As interações no rádio expandido: a experiência das emissoras curitibanas Massa FM, Caiobá FM e 98 FM - Bespalhok, Flávia Lúcia Bazan (2015)
This thesis aims at investigating the relationships that are established within the listening process in the expanded radio, understood as the one that overflows beyond the airwaves and reaches sites, microblogs, mobile phones and online social media. Drawing on literature review, the goal here is to contextualize the moment experienced by the vehicle by tracing its historical/technological path until the concepts of convergence (JENKINS, 2008), expanded radio (KISCHINHEVSKY, 2011a, 2011b) and interaction (BRAGA, 2000). The focus of the study covers three broadcasting stations of the capital city of Paraná state: Massa FM, Caiobá FM and 98 FM. It is also underpinned by an exploratory research with field survey. At first, the study was conducted by the listening of broadcasting stations excerpts and the analysis of their Facebook pages. Secondly, interviews were conducted with broadcast producers and communicators as well as observations and analysis of the social network Facebook. Both qualitative and quantitative researches were conducted in order to collect data from ordinary and virtual broadcast listeners. Among other results, it appears that the relationship between broadcast station/communicator and ordinary/virtual listeners are shifting due to the fact that information and communication technologies have diversified the access to broadcasters and communicators. It ended up strengthening the ties of affection and proximity with the listeners as well. Both the listeners and the radio speakers pointed out that the ease of participation is one of the features of the expanded broadcast stations. Radio station, listeners and Internet users acknowledge the digital social network Facebook as the best channel to establish relations in the current radio broadcast.